1996
DOI: 10.1046/j.1365-313x.1996.9060851.x
|View full text |Cite
|
Sign up to set email alerts
|

The hypersensitive reaction, membrane damage and accumulation of autofluorescent phenolics in lettuce cells challenged by Bremia lactucae

Abstract: Summary The expression of resistance to Bremia lactucae determined by the resistance genes Dm5/8 and Dm7 in lettuce was examined; incompatibility involved the hypersensitive reaction (HR) which occurred only within penetrated cells at early and late stages of fungal development, respectively. Autofluorescence observed under UV and blue light excitation in cells undergoing the HR was associated with the accumulation of ester‐linked syringaldehyde and caffeic acid on plant cell walls. Two phases of phenolic depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
83
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 0 publications
9
83
0
Order By: Relevance
“…Although, to our knowledge the accumulation of wall-bound benzyl alcohols has not been described in relation to pathogen defense, two benzaldehydes, 4-hydroxybenzaldehyde and vanillin (Fig. 2), along with unidentified wall components, have been isolated from fungal elicitortreated, cultured P. crispum (22) and S. tuberosum cells (23), as well as from fungus-infected S. tuberosum leaves (23), and syringaldehyde was found to accumulate in fungus-infected lettuce leaves (24). Further analysis in this direction may reveal additional, structurally related compounds, possibly including the products of BAD activity.…”
Section: Discussionmentioning
confidence: 98%
“…Although, to our knowledge the accumulation of wall-bound benzyl alcohols has not been described in relation to pathogen defense, two benzaldehydes, 4-hydroxybenzaldehyde and vanillin (Fig. 2), along with unidentified wall components, have been isolated from fungal elicitortreated, cultured P. crispum (22) and S. tuberosum cells (23), as well as from fungus-infected S. tuberosum leaves (23), and syringaldehyde was found to accumulate in fungus-infected lettuce leaves (24). Further analysis in this direction may reveal additional, structurally related compounds, possibly including the products of BAD activity.…”
Section: Discussionmentioning
confidence: 98%
“…This strong decline, together with the lack of an infection-induced increase of its wall-bound counterpart (9)-similar to the other two wall-bound cinnamate derivatives (7 and 8), but in contrast to most of the benzoate/benzaldehyde derivatives (1, 2, 4 and 6)-suggests a metabolic involvement of the three cinnamate residues (7-9) outside the presently investigated realms. The striking identity of their substitution patterns with those of the three characteristic lignin building blocks seems to indicate their direct or indirect involvement in the formation of lignin or of the less clearly defined 'lignin-like material', both of which have frequently been postulated to be re-enforced or newly formed as physical barriers around pathogen infection sites (Tiburzy and Reisener, 1990;Kovats et al, 1991;Bennett et al, 1996). Such a role of compounds 7-9 in lignin-related metabolism would readily explain not only their apparent lack of accumulation upon infection, but also the absence of detectable amounts of the corresponding aldehydes.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Bennett et al (1996) suggested that accumulation of bright autofluorescing material within the fungus cell wall in the lettuce-Bremia lactucae interaction correlated with strong leakage of phenolics from the host vacuole, leading to changes in ionic balance and formation of compounds with fungitoxic activity. The authors concluded that irreversible membrane damage in lettuce was a key signaling event leading to widespread activation of defense responses in surrounding cells.…”
Section: Discussionmentioning
confidence: 99%